2019
DOI: 10.2134/ael2018.10.0051
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Mixture Effects on Maize, Soybean, and Wheat Yield in Rotation

Abstract: M ultispecies cover crop mixtures are quickly gaining popularity in the United States. According to a national survey of cover crop users, adoption of multispecies mixtures increased 38% between 2012 and 2016 (CTIC and SARE, 2013; CTIC, 2017). Compared with traditional monoand biculture cover crops, mixtures have the potential to optimize across a wider range of ecosystem services, such as building soil organic matter, reducing N leaching, and improving yield of the following crop (Creamer et al., 1997; LaChan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…Therefore, soybean yields varied from year to year, but were not influenced by the presence of cover crops. This is consistent with previous research which has found soybean yields to be more resilient to a cereal rye cover crop than corn (Hunter et al., 2019; Singer & Kohler, 2005). Least squares mean soybean yield for each treatment and year are reported in Table 4.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, soybean yields varied from year to year, but were not influenced by the presence of cover crops. This is consistent with previous research which has found soybean yields to be more resilient to a cereal rye cover crop than corn (Hunter et al., 2019; Singer & Kohler, 2005). Least squares mean soybean yield for each treatment and year are reported in Table 4.…”
Section: Resultssupporting
confidence: 92%
“…The spring of 2017 was characterized by warmer than average temperatures and above average precipitation (Table 1), resulting in ideal growing conditions for the cereal rye cover crop. While previous literature is mixed with respect to the impact of cover crops on corn yield, our finding that cereal rye before corn may reduce corn yield in some years is certainly not unique (Hunter et al., 2019; Krueger, Ochsner, Porter, & Baker, 2011; Marcillo & Miguez, 2017; Singer & Kohler, 2005). Adaptive N fertilizer management and improved cover crop management, including species selection, the timing of cover crop termination, cover crop biomass removal, etc., may mitigate potential cash crop yield impacts.…”
Section: Resultsmentioning
confidence: 54%
“…Cover crops had no impact on soybean or wheat yields [35], so here we focus on CC impacts on N supply to maize. Maize was harvested for silage at 60–70% moisture from two subsamples of crop row at least 5.3 m in length.…”
Section: Methodsmentioning
confidence: 99%
“…Cover crop research has evaluated CC effects on soil quality 13 – 14 , 16 – 17 and crop production 16 , 18 – 22 . Long-term studies are needed to assess the potential of CCs to sequester C 4 , 23 – 25 and have primarily focused on evaluating the amount of soil C sequestered with CCs than control 26 – 28 rather than the change in SOC stock 29 .…”
Section: Introductionmentioning
confidence: 99%